Домашние и дикие животные из раскопок древнего города Родни на Княжьей горе - Корнеев, А.П. (Вестник зоологии, 1969)
The author analysed 12448 bone remains of domestic and wild animals from the excavations of the ancient Slavonic town Rodnya on Knyazhiya hill in Kanev. The majority of the bones are the kitchen remains. According to the data of the investigations the ancient Slavs from Rodnya used 24 species of animals (8 species of domastic animals and 16 species of wild ones) for their home needs.
Quantitative correlation of the bone remains of various animals permits concluding that in the farms of the Rodnya inhabitants, as well as in the farms of all East Slavonic settlements of the romensko-borshevsky type, the agriculture and cattle-breeding were predominant. The small steppe breed usually met in nomadic tribes prevailed among horses; the cattle was similar to big-breed group.
Wild animals, the bones of which were found in the excavations, were the hunting species, that testifies to a certain role of hunting in the life of the Rodnya Slavs, alongside with husbandry and cattle-breeding. Among the found bone remains of wild animals there is a small number of bones of fur-bearing animals (Castor fiber L., Vulpes vulpes L.). This makes it possible to suppose that hunting wild animals for the sake of meat prevailed at that time. That is why bone remains of such animals as Alces alces L., Cervas ela-phus L., Capreolus capreolus L., Sus crofa L. predominate in the excavations.